Perspektif al-Qur’an Tentang Anak Yatim dan Validitas Berpoligami: (Kajian Tafsir Tematik) - Siregar, Khairil Ikhsan (Jurnal Studi Al-Qur’an, 2008)
Al- Qur’an is the original Holy Book of Samawiy till the hereafter, guiding for humanity. It capables to explain more topics were written in ownself. One of this topics tells about Al- Qur’an’s perspective of fatherless (orphan) and validity of polygamist. Fatherless is one of created not productively in his life and he still needs concern from a father. And maybe he leaves with his mother but amount of a mother is not same with amount of a father. Therefor Allah legitimated a polygamy with a condition that he must be just for his wifes. In meaning of hadist from Imam al- Bukhoriy :"â€¦. Rasulullah in that manner speaks about himself, that I never said something was ill-gotten when Allah has said it was legitimated and I never said something was legitimated when Allah has said it was ill-gotten ". This research used by " Tafsir Thematic Method" concern about verses of Holy Qur’an for this topic and talk about correlation in between the verses and helped with the others knowledges such as nasikh wal mansukh (verse invalidate and verse invalidated) until found on the conclusion for this topic easily. Kata kunci : Anak Yatim, validalitas Poligami, Tafsir Tematik